THE RELATIONSHIP OF SEAFLOOR SURFACIAL SEDIMENT WITH SEABOTTOM MORPHOLOGY OF LEMKUTAN ISLAND WATER, WEST KALIMANTAN - Hananto Kurnio; Noor C.D. Aryanto (BULLETIN OF THE MARINE GEOLOGY, 2013)
Sea floor sediment surrounding Lemukutan Island, West Kalimantan is distributed on rather steep sea bottom morphology. The steep bottom seems a continuation of rugged morphology of the island, especially at the northeast and southeast parts. This paper discusses the relation between sediment grain sizes and the steepness of sea bottom morphology. Grain size analyses of sediment shows various sediment types such as slightly gravelly muddy sand, gravel mostly composed of coral and lithic, and gravelly sand. Results show that steepness of sea bottom slope control deposited sediment types, coarse fraction sediments tend to settle on the area of high slope angle as at the northeastern and southeastern of the island. On the other hand, high energy marine environment, such as at the sea in front of north headland of Lemukutan Island, tends to accumulate coarse sediments. High percentages of organism shells in marine sediments obviously are deposited at those two domains. Keywords: sea bottom morphology, sediment, Lemukutan Island, West Kalimantan. Sedimen dasar laut sekitar Pulau Lemukutan, Kalimantan Barat tersebar pada morfologi yang agak curam. Permukaan dasar laut yang curam tampaknya merupakan kelanjutan morfologi kasar pulau tersebut, terutama pada bagian timur laut dan tenggara. Makalah ini membahas hubungan antara besar butir sedimen dan kecuraman morfologi dasar laut. Analisis besar butir sedimen memperlihatkan jenis sedimen yang bervariasi, seperti pasir lumpuran sedikit krikilan, kerikil umumnya terdiri koral dan fragmen batuan, dan pasir krikilan. Hasil kajian menunjukkan bahwa kecuraman lereng dasar laut mengontrol tipe sedimen yang diendapkan, sedimen fraksi kasar cenderung mengendap pada daerah dengan sudut lereng tinggi seperti di bagian timur laut dan tenggara Pulau Lemukutan. Di samping itu, lingkungan laut enerji tinggi, seperti di bagian utara pulau, cenderung mengakumulasikan sedimen kasar. Prosentase tinggi dari cangkang organisma dalam sedimen laut tampak nyata diendapkan pada kedua lingkungan tersebut. Kata kunci: morfologi dasar laut, sedimen, Pulau Lemukutan, Kalimantan Barat.